A kind of ABS resin composition and its application
By combining ABS graft copolymer with specific unsaturation and grafting rate in ABS resin with aromatic vinyl-vinyl cyano copolymer, the problems of oxidation and discoloration and performance of ABS resin are solved, and excellent Heat resistance and weather resistance.
Patent Information
- Application Number
- CN202411480257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-23
AI Technical Summary
ABS resins have caused oxidative discoloration and macroscopic performance due to their unique island structure. The existing methods are solved by adding additives but are costly and unstable in performance.
ABS resin composition is formed by combining a low unsaturation ABS graft copolymer with a specific unsaturation and grafting rate with an aromatic vinyl-vinyl cyano copolymer.
It improves the heat resistance, yellowing resistance and weather resistance of ABS resin, extends the oxidation induction time, and enhances the overall performance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an ABS resin composition and application thereof. Background Art
[0002] ABS resin is composed of three components: butadiene (B), styrene (S) and acrylonitrile (A). Butadiene rubber forms a unique island structure that can resist impact, acrylonitrile gives the resin certain thermal stability and weather resistance, and styrene provides the resin with fluidity during processing. ABS resin is widely used in the automotive, electronic and electrical industries due to its excellent comprehensive performance, but it is also this structure that causes ABS resin to have certain disadvantages. Since butadiene monomer has two double bonds, there is still a certain amount of residual double bonds in ABS resin after the reaction. This double bond structure makes the resin easy to oxidize and discolor, and at the same time causes its macroscopic properties such as tensile and impact to decline.
[0003] At present, the solution to this shortcoming of ABS resin is mostly through the addition of some additives such as light stabilizers and ultraviolet absorbers. For example, in order to overcome the problem that ABS resin is prone to degradation, aging, discoloration and even cracking under long-term light, which leads to the decline of physical properties, Chinese patent CN101709133A chooses to add a series of light stabilizers, ultraviolet absorbers, etc. to ABS materials. However, the addition of additives not only increases the cost, but also the additives are easy to precipitate, resulting in unstable heat resistance and heat aging resistance of the material and short service life. Therefore, in addition to adding additives, it is also necessary to consider improving the heat aging resistance of ABS polymer itself, so as to fundamentally solve the problem that ABS resin is easy to oxidize and discolor, and the decline of macroscopic properties such as tensile and impact.
[0004] Therefore, developing a material that can fundamentally solve the poor heat resistance, yellowing resistance and weather resistance of ABS resin is an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide an ABS resin composition and its application. In the present invention, the material comprising the ABS resin composition has excellent heat resistance, yellowing resistance and weather resistance, and a long oxidation induction time.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an ABS resin composition, which comprises, by weight, 20 to 35 parts of a low-unsaturation ABS graft copolymer and 65 to 80 parts of an aromatic vinyl-vinyl cyanide copolymer; the unsaturation of the low-unsaturation ABS graft copolymer is 0.1 to 10 mol / g; and the grafting rate of the low-unsaturation ABS graft copolymer is 20 to 60%.
[0008] In the present invention, an ABS graft copolymer with a specific unsaturation degree and grafting rate is compounded with an aromatic vinyl-vinyl cyanide copolymer, and the obtained ABS resin material has excellent heat resistance and heat aging resistance and a long oxidation induction time.
[0009] In parts by weight, the ABS resin composition includes 20 to 35 parts of the low-unsaturation ABS graft copolymer, for example, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, etc., preferably 22 to 32 parts, and more preferably 25 to 30 parts.
[0010] In parts by weight, the ABS resin composition includes 65 to 80 parts of the aromatic vinyl-vinyl cyanide copolymer, for example, 65 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, etc., preferably 66 to 76 parts, and more preferably 68 to 74 parts.
[0011] The unsaturation degree of the low-unsaturation ABS graft copolymer is 0.1-10 mol / g, for example, 0.1 mol / g, 0.2 mol / g, 0.5 mol / g, 1 mol / g, 1.5 mol / g, 2 mol / g, 2.5 mol / g, 3 mol / g, 3.5 mol / g, 4 mol / g, 4.5 mol / g, 5 mol / g, 5.5 mol / g, 6 mol / g, 6.5 mol / g, 7 mol / g, 7.5 mol / g, 8 mol / g, 8.5 mol / g, 9 mol / g, 9.5 mol / g, 10 mol / g, etc.; the grafting rate of the low unsaturation ABS graft copolymer is 20-60%, and the grafting rate is 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, etc.
[0012] Preferably, the unsaturation degree of the low-unsaturation ABS graft copolymer is 1-8 mol / g, preferably 3-7.8 mol / g, further preferably 3.1-7 mol / g, more preferably 3.15-5.6 mol / g, particularly preferably 3.2-5 mol / g.
[0013] Preferably, the grafting rate of the low-unsaturation ABS graft copolymer is 22-55%, preferably 25-54%, more preferably 30-53%, and more preferably 40-52%.
[0014] In the present invention, the unsaturation and grafting rate of the low-unsaturation ABS graft copolymer are within the above-defined ranges, and have a longer oxidation induction period, the oxidation induction time is ≥20 min, preferably the oxidation induction time is ≥25 min, further preferably the oxidation induction time is ≥30 min, more preferably the oxidation induction time is ≥40 min, and particularly preferably the oxidation induction time is ≥45 min.
[0015] Preferably, the raw materials for preparing the low-unsaturation ABS graft copolymer include butadiene latex, comonomer and initiator; based on 100 parts of the dry basis of the butadiene latex, the amount of the comonomer is 20 to 150 parts (for example, it can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 90 parts, 100 parts, 120 parts, 140 parts, 150 parts, etc., preferably 30 to 80 parts, more preferably 40 to 65 parts), and the amount of the initiator is 0.5 The amount of the present invention may be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 9.5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 28, 30, 32, 34, 35, 36, 38, 40, 42, 44, 46, etc., preferably 3 to 46 parts, more preferably 9 to 46 parts.
[0016] Preferably, the initiator comprises at least one of an oil-soluble initiator, a redox initiator or a water-soluble initiator.
[0017] Preferably, the relationship between the amount of the initiator used, the theoretical grafting rate of the low-unsaturation ABS graft copolymer and the content of the butadiene latex satisfies the following formula.
[0018] E=E1+E2+E3 30%≤x<100%.
[0019] E=E4 0%<x<30%.
[0020] Where E1=e (1.5 / y) log(1 / x); E2=E 21 +E 22 , E 21 =e (1 / y) log(1 / x); E 22 =e (0.8 / y) log(1 / x); E3=e (2 / y) log(1 / x); E4 = e (2 / y) log(1 / x).
[0021] Wherein, x is the theoretical grafting rate of low unsaturation ABS graft copolymer, y is the mass of butadiene latex / the total mass of butadiene latex and comonomer; E is the total amount of initiator; E1 is the amount of oil-soluble initiator; E2 is the amount of redox initiator; E 21 is the amount of oxidant in the redox initiator; E 22 is the amount of reducing agent in the redox initiator; E3 is the amount of water-soluble initiator; E4 is the amount of any one of the oil-soluble initiator, redox initiator or water-soluble initiator.
[0022] In the present invention, the theoretical grafting rate in the above formula is the target grafting rate. For example, if a low-unsaturation ABS graft copolymer with a target grafting rate of 30% is desired, then the theoretical grafting rate x=30%.
[0023] In the present invention, when a low unsaturation ABS graft copolymer with a target grafting rate of less than 30% is to be obtained, a single initiator system is used, that is, the initiator is selected from any one of an oil-soluble initiator, a redox initiator or a water-soluble initiator; the initiator content adopts the formula E=E4.
[0024] When a low-unsaturation ABS graft copolymer with a target grafting rate ≥30% is to be obtained, a composite initiator system is used, that is, an oil-soluble initiator, a redox initiator and a water-soluble initiator are composited; the initiator content is calculated using the formula E=E1+E2+E3; a composite initiator is used, and the contents of different initiators satisfy the above formula, and the actual grafting rate of the obtained ABS graft copolymer is closer to the theoretical grafting rate; and the closer the actual grafting rate to the theoretical grafting rate can ensure that more monomers and initiators participate in the reaction, avoid the influence of small molecules or monomer residues on the performance of the ABS graft copolymer, avoid raw material waste, and reduce costs; and, by using a composite initiator, an ABS graft copolymer with a higher grafting rate can be obtained, thereby making the oxidation induction time of the material longer; and a single initiator system is suitable for obtaining ABS graft copolymers with a lower grafting rate. Even if the theoretical grafting rate is increased (greater than 30%), the actual grafting rate will still be lower than 30%.
[0025] Preferably, the oil-soluble initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, benzoyl peroxide or di(2-ethylhexyl) peroxydicarbonate.
[0026] Preferably, the water-soluble initiator includes at least one of potassium persulfate, ammonium persulfate, hydrogen peroxide, sodium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid or azobisisopropylimidazoline.
[0027] Preferably, in the redox initiator, the oxidant includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, benzoyl peroxide or di(2-ethylhexyl) peroxydicarbonate; and the reducing agent includes at least one of ferrous sulfate, ferric chloride, sodium formaldehyde sulfoxylate, sodium metabisulfite, fructose or tetraethylpentanediamine.
[0028] In the present invention, when a composite initiator is used, it is preferred to add different types of initiators at different reaction stages to initiate the reaction; when there is no reducing agent in the system, it indicates that an oil-soluble initiator is used to initiate the reaction, and the amount of the oil-soluble initiator is calculated according to the formula E1=e (1.5 / y) log(1 / x) calculation; when the system also includes a reducing agent, it indicates that a redox initiator is used for the initiator reaction. At this time, the amount of the oxidant is calculated according to the formula E 21 =e (1 / y) log(1 / x) calculation.
[0029] Preferably, the butadiene-based latex includes at least one of polybutadiene latex, styrene-butadiene latex or nitrile-butadiene latex.
[0030] In the present invention, the solid content of the butadiene latex is 20-65%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc.; more preferably, it is 25-62%, and more preferably, it is 30-59%.
[0031] Preferably, the gel content of the butadiene latex is 32-90%, for example, it can be 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., more preferably 50-85%, and more preferably 60-82%.
[0032] Preferably, the ratio of D50 particle size to D90 particle size of the butadiene latex is 0.5-0.92, for example, it can be 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, etc., more preferably 0.62-0.8, and more preferably 0.64-0.76.
[0033] In the present invention, when the gel content of the butadiene-based latex and the ratio of the D50 particle size to the D90 particle size are out of the above ranges, the oxidation induction time of the ABS resin composition becomes shorter.
[0034] Preferably, the D50 particle size of the butadiene-based latex is 100-800 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, etc.
[0035] Preferably, the comonomer includes at least two of styrene and its derivatives, acrylonitrile and its derivatives or alkyl (meth)acrylate, and at least includes styrene and its derivatives.
[0036] In the present invention, the mass percentage of styrene and its derivatives in the comonomer is 60-90%, for example, it can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, etc.; preferably, it is 65-85%, and more preferably, it is 70-80%.
[0037] In the present invention, the styrene and its derivatives include but are not limited to at least one of styrene, α-methylstyrene, and 2-methylstyrene; the acrylonitrile and its derivatives include but are not limited to acrylonitrile and / or methacrylonitrile; the (meth) alkyl acrylate includes but is not limited to at least one of methyl methacrylate, butyl acrylate, or butyl methacrylate.
[0038] Preferably, based on 100 parts of the dry basis of the butadiene latex, the raw materials for preparing the low-unsaturation ABS graft copolymer also include 0.5 to 2 parts of an emulsifier (for example, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, etc.) and 0.01 to 0.5 parts of a chain transfer agent (for example, 0.01 parts, 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.).
[0039] In the present invention, the emulsifier includes one or more of anionic surfactants, nonionic surfactants and polymer surfactants. Among them, the anionic surfactant includes but is not limited to potassium rosinate, potassium oleate, potassium stearate, sodium stearate, sodium dodecylbenzene sulfonate or fatty acid potassium, etc.; the nonionic surfactant includes but is not limited to polyoxyethylene ethers, such as alkylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, long-chain fatty alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether, etc.; the polymer surfactant includes but is not limited to polyether, polystyrene-polyoxyethylene block copolymer or polyisobutylene-polyoxyethylene block copolymer, etc.
[0040] In the present invention, the chain transfer agent includes sulfur-containing chain transfer agents, such as dodecanethiol, thioglycolic acid, mercaptopropionic acid, sodium bisulfite, mercaptoethanol, mercaptopropanol, etc.; and / or, sulfur-free chain transfer agents, such as formic acid, sodium hypophosphite, etc.
[0041] Preferably, based on 100 parts of the dry basis of the butadiene latex, the preparation raw materials also include 5 to 15 parts of auxiliary agents, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc., more preferably 6 to 13 parts, more preferably 8 to 12 parts, and particularly preferably 9.5 to 10.5 parts.
[0042] Preferably, the auxiliary agent includes at least one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate or diethylenetriamine pentacarboxylate.
[0043] In the present invention, the auxiliary agent can be used as an electrolyte, a pH stabilizer, a metal chelating agent, and the like.
[0044] Preferably, the low-unsaturation ABS graft copolymer is prepared by the following method, which includes the following steps.
[0045] The butadiene latex, comonomer and initiator are mixed and reacted to obtain the low-unsaturation ABS graft copolymer.
[0046] Preferably, the mixed material further comprises at least one of an emulsifier, a chain transfer agent or an auxiliary agent.
[0047] Preferably, the reaction comprises: mixing butadiene latex, comonomer, initiator A, emulsifier and chain transfer agent and optional auxiliary agent, carrying out a first stage reaction, then adding initiator B thereto, carrying out a second stage reaction, adding initiator C thereto, carrying out a third stage reaction, and obtaining the low unsaturation ABS graft copolymer; the initiator A and the initiator B are each independently selected from an oil-soluble initiator or a redox initiator; and the initiator C is selected from a water-soluble initiator.
[0048] In the present invention, different types of initiators are added in stages, that is, oil-soluble initiators or redox initiators are added in the first two reactions, and water-soluble initiators are added in the third reaction. The obtained ABS graft copolymer has a higher grafting rate and a lower unsaturation.
[0049] Preferably, among the initiator A and the initiator B, one is an oil-soluble initiator, and the other is a redox initiator.
[0050] Preferably, the temperature of the first stage reaction is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the time is 10-60 min, for example, 10 min, 15 min, 20 min, 25min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0051] In the present invention, the reaction is carried out in a solvent, and the weight portion of the solvent is 150 to 200 parts.
[0052] Preferably, the temperature of the second stage reaction is 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the time is 60-240 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min, etc.
[0053] Preferably, the temperature of the third stage reaction is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the time is 50-150 min, for example, 50 min, 60 min, 80 min, 100 min, 120 min, 140 min, 150 min, etc.
[0054] Preferably, after the reaction is completed, the method further comprises the step of coagulating the obtained latex.
[0055] In the present invention, the coagulation comprises adding 1 to 10 parts of an antioxidant emulsion (for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc., preferably 2 to 8 parts, more preferably 4 to 6 parts) to the latex obtained by the reaction, and then adding 1 to 10 parts of a flocculant thereto for coagulation, washing and drying to obtain the low-unsaturation ABS graft copolymer; wherein the contents of the antioxidant emulsion and the flocculant are each independently calculated based on 100 parts of the dry basis of the latex obtained by the reaction.
[0056] In the present invention, the flocculant includes but is not limited to one or more of sulfuric acid, hydrochloric acid, acetic acid, calcium sulfate, magnesium sulfate, calcium carbonate or calcium chloride.
[0057] In the present invention, the amount of the initiator in each stage is calculated by the above formula, and a high grafting rate is achieved on the polybutadiene latex with a high gel content, thereby obtaining an ABS graft copolymer with a high grafting rate and low unsaturation, thereby improving the heat resistance, weather resistance and yellowing resistance of the ABS resin composition.
[0058] In the present invention, it is preferred to adopt a composite initiation system, combined with the initiation efficiency of different initiators at different sites, so as to realize allyl position hydrogen abstraction graft polymerization in addition to double bond graft polymerization. Further, by composite redox initiation system, graft copolymerization can be carried out on high gel content butadiene latex in stages and composite ratio initiation mode, so as to obtain a graft latex with low double bond content and high grafting rate. After the obtained graft latex is subjected to coagulation and other treatments, a low unsaturation ABS graft copolymer is obtained, and the ABS resin composition including the low unsaturation ABS graft copolymer has excellent heat resistance, weather resistance and yellowing resistance.
[0059] Preferably, the ABS resin composition further comprises 0-3 parts of other additives in parts by weight, for example, 0 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc., more preferably 0.5-2.5 parts, and more preferably 1-2 parts.
[0060] Preferably, the other auxiliary agents include antioxidants and / or lubricants.
[0061] In the present invention, the antioxidant includes but is not limited to at least one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 445, and antioxidant 1098.
[0062] In the present invention, the lubricant includes but is not limited to at least one of ethylene bisstearamide, erucamide, zinc stearate or silicone oil.
[0063] Preferably, the oxidation induction time of the ABS resin composition is ≥12 min, preferably ≥20 min, further preferably ≥30 min, more preferably ≥35 min, or ≥40 min, particularly preferably ≥45 min.
[0064] In a second aspect, the present invention provides an ABS resin heat-resistant material, wherein the ABS resin heat-resistant material comprises the ABS resin composition according to the first aspect.
[0065] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] Compared with the prior art, the present invention has the following beneficial effects: the ABS resin composition provided by the present invention adopts an ABS graft copolymer with a specific unsaturation degree and grafting rate and an aromatic vinyl-vinyl cyanide copolymer compounded in a specific content, and the obtained ABS resin material has excellent heat resistance and heat aging resistance, and a long oxidation induction time. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Unless otherwise specified, the materials used in the present invention can be purchased from the market or prepared by conventional methods; the materials used in the present invention are as follows: polybutadiene latex is prepared, and the others are commercially available.
[0069] Polybutadiene latex: prepared in the laboratory, the preparation method is as follows: 90 parts of butadiene, 3.5 parts of initiator di-tert-butyl peroxide, 3 parts of electrolyte potassium carbonate, 4.5 parts of emulsifier potassium disproportionate rosin acid, 1.2 parts of chain transfer agent tert-dodecyl mercaptan, 200 parts of deionized water and 0-5 parts of hydroxyethyl acrylate are added to the reactor and mixed evenly, and the temperature is raised to 80°C. When the conversion rate is ≥95%, polybutadiene latex is obtained. Among them, A1-A4 polybutadiene latex is obtained by adjusting the amount of hydroxyethyl acrylate to 0.15 parts, 0.4 parts, 0.7 parts, and 1.3 parts, respectively, wherein the average particle size range of A1-A4 latex is 300 nm±50nm.
[0070] A1: Gel content 80%, D50 particle size / D90 particle size 0.65.
[0071] A2: Gel content 70%, D50 particle size / D90 particle size 0.71.
[0072] A3: Gel content 65%, D50 particle size / D90 particle size 0.75.
[0073] A4: Gel content 40%, D50 particle size / D90 particle size 0.9.
[0074] Antioxidant emulsion: ARTNOX50L, Guangdong Nochi Chemical Co., Ltd.
[0075] Calcium chloride: purity 97%, Shanghai Darui Fine Chemicals Co., Ltd.
[0076] In the present invention, the unsaturation test method refers to the industry standard: SH / T 1763-2020, "Iodine value method for determination of residual unsaturation in hydrogenated nitrile rubber (HNBR)"; the gel content test refers to the industry standard: SH / T 1050-2014, "Determination of gel content of synthetic raw rubber"; the grafting rate test method is as follows: after the ABS grafted latex is purified three times using the organic solvent butanone, the ratio of the dry weight of the remaining polymer to the dry weight of the initial polymer (i.e., butadiene latex); the D50 particle size and D90 particle size of the polybutadiene latex are obtained by testing with a laser nanoparticle size analyzer.
[0077] Preparation Example: Preparation of low unsaturation ABS graft copolymer.
[0078] ABS1~ABS22, in parts by weight, the raw material types and amounts of ABS1~ABS22 are shown in Tables 1~3; wherein, " / " indicates that the component is not included in the formula; the preparation method of the low-unsaturation ABS graft copolymer comprises: according to the formula amount, polybutadiene latex, comonomer, emulsifier, chain transfer agent and solvent (desalted water, content is 200 parts) are added to the reactor in sequence, after heating to 50°C, adding oil-soluble initiator to react for 30 minutes, then adding redox initiator to the reaction system, reacting at 55°C for 240 minutes, continuing to add water-soluble initiator to the reaction system, and reacting at 70°C for 80 minutes; after the reaction is completed, adding 5 parts of antioxidant emulsion thereto, and then adding 5 parts of calcium chloride, and condensing at 90°C to obtain the low-unsaturation ABS graft copolymer.
[0079] Among them, the reaction conditions of ABS1~ABS22 are shown in Tables 1~3.
[0080] Table 1
[0081]
[0082] Table 2
[0083]
[0084] Table 3
[0085]
[0086] Examples 1 to 24.
[0087] Examples 1 to 24 respectively provide an ABS resin composition, and the formula of the ABS resin composition is shown in Table 4 in parts by weight.
[0088] Unless otherwise specified, the materials used in the examples and comparative examples of the present invention are as follows.
[0089] Aromatic vinyl-vinyl cyanide copolymer: AS resin, brand: KFA-130H.
[0090] The auxiliary agents used are: antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.
[0091] The lubricant is ethylene bis stearamide.
[0092] The low-unsaturation ABS graft copolymers used in Examples 1 to 22 are ABS1 to ABS22, respectively, and the low-unsaturation ABS graft copolymers used in Examples 23 and 24 are ABS1, respectively.
[0093] Table 4
[0094]
[0095] Performance test: The oxidation induction time of the ABS resin of the ABS resin composition provided in Examples 1 to 24 was tested. The test was based on the national standard: GB / T 19466.6-2009, "Plastics Differential Scanning Calorimetry (DSC) Part 6: Determination of Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)".
[0096] The specific test results are shown in Table 5.
[0097] Table 5
[0098]
[0099] As can be seen from Table 5, the ABS resin composition provided by the present invention, which is compounded with an ABS graft copolymer having a specific degree of unsaturation and grafting rate and an aromatic vinyl-vinyl cyanide copolymer in a specific content, has excellent heat resistance and heat aging resistance, and has a long oxidation induction time, which is ≥12 min, preferably ≥20 min, further preferably ≥40 min, and more preferably ≥45 min.
[0100] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An ABS resin composition, characterized in that: The ABS resin composition comprises, by weight, 20 to 35 parts of a low-unsaturation ABS graft copolymer and 65 to 80 parts of an aromatic vinyl-vinyl cyanide copolymer; The unsaturation degree of the low-unsaturation ABS graft copolymer is 0.1-10 mol / g; The grafting rate of the low-unsaturation ABS graft copolymer is 20-60%; The raw materials for preparing the low-unsaturation ABS graft copolymer include butadiene latex, comonomer and initiator; The gel content of the butadiene latex is 32-90%; The ratio of the D50 particle size to the D90 particle size of the butadiene latex is 0.5-0.
92.
2. The ABS resin composition according to claim 1, characterized in that The unsaturation degree of the low-unsaturation ABS graft copolymer is 1-8 mol / g.
3. The ABS resin composition according to claim 1, characterized in that: The grafting rate of the low-unsaturation ABS graft copolymer is 22-55%.
4. The ABS resin composition according to claim 1, characterized in that: Based on 100 parts of the dry basis of the butadiene latex, the amount of the comonomer is 20 to 150 parts, and the amount of the initiator is 0.5 to 46 parts.
5. The ABS resin composition according to claim 1, characterized in that: The initiator includes at least one of an oil-soluble initiator, a redox initiator or a water-soluble initiator.
6. The ABS resin composition according to claim 1, characterized in that: The relationship between the amount of the initiator used, the theoretical grafting rate of the low-unsaturation ABS graft copolymer and the content of the butadiene latex satisfies the following formula: E=E1+E2+E3 30%≤x<100%; E=E4 0%<x<30%; in, E1=e (1.5 / y) log(1 / x); E2=E 21 +E 22 ,AND 21 =and (1 / y) log(1 / x);And 22 =and (0.8 / y) log(1 / x); E3=e (2 / y) log(1 / x); E4= e (2 / y) log(1 / x) Wherein, x is the theoretical grafting rate of low unsaturation ABS graft copolymer, y is the mass of butadiene latex / the total mass of butadiene latex and comonomer; E is the total amount of initiator; E1 is the amount of oil-soluble initiator; E2 is the amount of redox initiator; E 21 is the amount of oxidant in the redox initiator; E 22 is the amount of reducing agent in the redox initiator; E3 is the amount of water-soluble initiator; E4 is the amount of any one of the oil-soluble initiator, redox initiator or water-soluble initiator.
7. The ABS resin composition according to claim 6, characterized in that: The oil-soluble initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, benzoyl peroxide or di(2-ethylhexyl) peroxydicarbonate.
8. The ABS resin composition according to claim 6, characterized in that: The water-soluble initiator includes at least one of potassium persulfate, ammonium persulfate, hydrogen peroxide, sodium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid or azobisisopropylimidazoline.
9. The ABS resin composition according to claim 6, characterized in that: In the redox initiator, the oxidant includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, benzoyl peroxide or di(2-ethylhexyl) peroxydicarbonate; and the reducing agent includes at least one of ferrous sulfate, ferric chloride, sodium formaldehyde sulfoxylate, sodium metabisulfite, fructose or tetraethylpentanediamine.
10. The ABS resin composition according to claim 1, characterized in that: The butadiene latex includes at least one of polybutadiene latex, styrene butadiene latex or nitrile butadiene latex.
11. The ABS resin composition according to claim 1, characterized in that: The D50 particle size of the butadiene latex is 100-800 nm.
12. The ABS resin composition according to claim 1, characterized in that: The comonomer includes at least two of styrene and its derivatives, acrylonitrile and its derivatives or alkyl (meth)acrylate, and at least includes styrene and its derivatives.
13. The ABS resin composition according to claim 1, characterized in that: Based on 100 parts of the dry basis of the butadiene latex, the raw materials for preparing the low-unsaturation ABS graft copolymer also include 0.5 to 2 parts of an emulsifier and 0.01 to 0.5 parts of a chain transfer agent.
14. The ABS resin composition according to claim 13, characterized in that: Based on 100 parts of the dry basis of the butadiene latex, the preparation raw material further includes 5 to 15 parts of an auxiliary agent; The auxiliary agent includes at least one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate or diethylenetriamine pentacarboxylate.
15. The ABS resin composition according to claim 1, characterized in that: The low-unsaturation ABS graft copolymer is prepared by the following method, which comprises the following steps: The butadiene latex, comonomer and initiator are mixed and reacted to obtain the low-unsaturation ABS graft copolymer.
16. The ABS resin composition according to claim 15, characterized in that: The mixed material also includes at least one of an emulsifier, a chain transfer agent or an auxiliary agent; The auxiliary agent includes at least one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate or diethylenetriamine pentacarboxylate.
17. The ABS resin composition according to claim 15, characterized in that: The reaction includes: The butadiene latex, comonomer, initiator A, emulsifier, chain transfer agent and optional auxiliary agent are mixed to carry out the first stage reaction, and then initiator B is added thereto to carry out the second stage reaction, and then initiator C is added thereto to carry out the third stage reaction to obtain the low unsaturation ABS graft copolymer; the initiator A and the initiator B are independently selected from oil-soluble initiators or redox initiators; the initiator C is selected from water-soluble initiators.
18. The ABS resin composition according to claim 17, characterized in that: The temperature of the first stage reaction is 40-80°C and the time is 10-60 min.
19. The ABS resin composition according to claim 17, characterized in that: The temperature of the second stage reaction is 50-80°C and the time is 60-240 min.
20. The ABS resin composition according to claim 17, characterized in that: The temperature of the third stage reaction is 60-90° C. and the time is 50-150 min.
21. The ABS resin composition according to claim 17, characterized in that: After the reaction is completed, the step of coagulating the obtained latex is also included.
22. The ABS resin composition according to claim 1, characterized in that: The ABS resin composition further comprises 0 to 3 parts of other additives by weight.
23. The ABS resin composition according to claim 22, characterized in that: The other adjuvants include antioxidants and / or lubricants.
24. The ABS resin composition according to claim 1, characterized in that: The oxidation induction time of the ABS resin composition is ≥12 min.
25. An ABS resin heat-resistant material, characterized in that: The ABS resin heat-resistant material comprises the ABS resin composition according to any one of claims 1 to 24.
Citation Information
Patent Citations
Excellent anti-aging ABS composite material and preparation method thereof
CN101709133A
Thermoplastic resin, preparation method therefor, and thermoplastic resin composition containing same
CN107075181A
Resin composition comprising modified ABS resin and polyamide resin
JP1992126757A
Cited By
Preparation method of transparent ABS (Acrylonitrile Butadiene Styrene) grafted rubber powder
CN121021763A